BLENDED LEARNING AND FEATURES OF THE USE OF THE ROTATION MODEL IN THE EDUCATIONAL PROCESS - Tkachuk, Г.В. (Journal of Information Technologies in Education (ITE), 2017)
The article analyzes of the problem of blended learning in higher education institutions. In particular, the article analyzes the legislative documents about the implementation of information technologies in the educational process, strategies for higher education, the introduction of distance learning, that determine importance of blended learning. The author also analyzes the concept of blended learning based on the definitions that are considered in the scientific and pedagogical literature. That analysis determines the ambiguity and incorrectness of the different definitions. It was proposed author's definition for this term. For order to identify the benefits of blended learning, it was analyzed of the positive and negative aspects of all technologies that are combined in the system of blended learning. Based on the analysis of different learning models, it was determined that the most optimal models is the station rotation model and the flipped classroom. The article provides an example of the use of a combination of these models for learning the topic "Computer Structure" by the students of the direction of training "Informatics". The education session was taking place in several stages and involves changing the five stations. Based on the conducted research was identified the general didactic and methodical principles of organization of blended learning.